Determination of nozzle angle for flow performance in supersonic subsea compact wet gas separator - Mohd Hashim, F.M. (Trans Tech Publications Ltd, 2014)
Flow assurances in deep water pipeline have received greater attention in oil and gas industry in order to meet the optimum production of hydrocarbons. However, existence of free water in the gas pipeline decreases production output and increases operational cost and time. Alternatively, anew supersonic subsea compact wet gas separator is design to remove free water from gas transmission pipeline. The key parts of the new design separators is the nozzle.The performanceof supersonic flow is highly related on the design of the nozzle. Therefore, the objective of this paper isto find correlation between the angle of the nozzle against separator flow performance, namely velocity. From the analysis done, it can be concluded thatat nozzle angle of 15Â°, maximum velocity is achievedthus producing supersonic flow. Â© (2014) Trans Tech Publications, Switzerland.